(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
This article provides a substantiated rationale for incorporating elements of mental fitness into the training regimen of athletes specializing in futsal. The relevance of this study is underscored by the growing need to optimize both the physical and psycho-emotional conditioning of players amid increasingly demanding training loads and congested competitive schedules. Conventional futsal training primarily emphasizes the development of speed-strength qualities, endurance, and technical-tactical proficiency. However, comparatively little attention is devoted to joint mobility, flexibility, mental well-being, and effective recovery strategies. This study aimed to assess the perceptions of players and coaches regarding the implementation of mental fitness practices—specifically yoga and stretching—with the goal of integrating them into the structured training process. The study involved 43 participants: 22 players from NFC “Uragan,” 15 from “Uragan-2-KFV,” and 6 members of the coaching staff. The research methodology included an analysis of scientific and methodological literature, sociological tools (surveys and interviews), and subsequent generalization and systematization of the collected data. Findings revealed that a significant number of athletes recognized the positive effects of mental fitness exercises on coordination, flexibility, and concentration—factors that contribute to overall performance readiness. However, the study also identified a low level of awareness and understanding of yoga and mental fitness concepts among participants, highlighting the need for broader educational efforts in this area. The results demonstrate the potential of mental fitness practices to reduce injury risk, alleviate psycho-emotional stress, and enhance functional readiness in futsal players. The study supports the development and integration of a specialized fitness program incorporating yoga-based elements, aligned with the specific demands of futsal. Evidently, the adoption of yoga and stretching into futsal training paradigms represents a valuable component of contemporary fitness support, fostering a more holistic approach to physical and mental conditioning. Future research should focus on designing targeted mental fitness programs that consider players’ functional status, positional roles, and training periodization.